Point and find: the intuitive user experience in accessing spatially structured dialect dictionaries - Wandl-Vogt, Eveline (Slavia Centralis, 2020)
This article adresses a long-term project of the "Austrian Academic Dialect Dictionary" the "Wörterbuch der bairischen Mundarten in Österreich (WBÖ / Dictionary of Bavarian dialects in Austria)". The project Datenbank der bairischen Mundarten (DBÖ / Database of Bavarian dialects in Austria) commenced in 1993 and was aimed at the digitalisation of the archives. In 1998 a rationalisation concept was issued, which targeted the completion of the dictionary in 2020 as a (virtual) unit consisting of the printed dictionary and a complementary database.The project Database of Bavarian dialects in Austria electronically mapped (dbo@ema) has demonstrated how the unification of online dictionaries and source material databases with visual, geo-referenced access applications and so called 'topographic navigation' can increase usability and lead to greater interdisciplinary insight.
Keywords: dialect lexicography; language mapping; user needs; topographic navigation